International Symposium on Geodesy for Earthquake and Natural Hazards (GENAH) : proceedings of the International Symposium on Geodesy for Earthquake and Natural Hazards (GENAH), Matsushima, Japan, 22-26 July, 2014 - Hashimoto, Manabu (International Association of Geodesy symposia., 2017)
These proceedings contain a selection of peer-reviewed papers presented at the International Symposium on Geodesy for Earthquake and Natural Hazards (GENAH), Matsushima, Japan, 22-26 July, 2014. The scientific sessions focused on monitoring temporal and spatial changes in Earth's lithosphere and atmosphere using geodetic satellite systems, high rate GNSS as well as high resolution imaging (InSAR, Lidar). Researchers in various fields of geodesy discussed the role of geodesy in disaster mitigation and how groups with different techniques can collaborate toward such a goal.- Resumé vydavatel